Analisis Kemampuan Berpikir Kritis Siswa dalam Menyelesaikan Masalah Numerasi Ditinjau dari Tingkat Self-Esteem - Nova Sasikarini, Diah; Firdaus, Hana Puspita Eka; Imamah Ah, Nurul Imamah Ah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze students' critical thinking skills in solving numeracy problems in terms of self-esteem levels. This study uses a qualitative descriptive approach with 25 eleventh-grade students of SMAN 1 Asembagus selected through purposive sampling technique based on high, medium, and low self-esteem categories. Data were collected through self-esteem questionnaires, numeracy essay tests, and interviews. The critical thinking ability indicators used refer to the six Facione indicators, namely interpretation, analysis, evaluation, inference, explanation, and self-regulation. The results show that students with high self-esteem are able to fulfill all critical thinking indicators completely, demonstrated by understanding the problem context, calculation accuracy, drawing logical conclusions, and the ability to reflect on the solution process. Students with medium self-esteem only fulfill some indicators, especially in interpretation, analysis, and evaluation, but are still weak in explanation and self-regulation. Meanwhile, students with low self-esteem tend to only fulfill the basic indicators and are not yet able to provide coherent explanations or recheck their work. The conclusion of this study shows that the level of self-esteem is related to the quality of students' critical thinking skills in solving numeracy problems, where the higher the student's self-esteem, the more complete the achievement of critical thinking indicators. This finding emphasizes the importance of paying attention to affective aspects, especially self-esteem, in efforts to improve the quality of mathematics learning and strengthen numeracy. Keywords: Critical Thinking, Numeracy, Self-esteem